Flexible liquid-based conductive wire harness and method of making the same

CN122968040APending Publication Date: 2026-10-23HEBI THB INT ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611271024.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0010]针对上述的技术问题,本发明提出一种柔性液基导电线束及其制备方法,用于解决现有技术中液态金属线束在大拉伸条件下存在内部导电介质断流失效和端子连接处漏液的问题

Benefits of technology

[0028]1.本发明通过在弹性管体内壁设置微米级螺旋沟槽,利用沟槽的毛细力束缚液态导电浆料,使线束在超大拉伸形变过程中液态导电浆料始终沿内腔连续分布,避免了因浆料局部聚集或断流导致的导电失效,实现了0~700%应变范围内的稳定导电。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968040A_ABST
    Figure CN122968040A_ABST
Patent Text Reader

Abstract

The application provides a flexible liquid-based conductive wire harness and a preparation method thereof, and the flexible liquid-based conductive wire harness comprises an elastic tube body and a liquid conductive slurry filled in the elastic tube body, both ends of the elastic tube body are respectively provided with a terminal, the terminal is electrically connected with the liquid conductive slurry, and the inner wall of the elastic tube body is provided with a micron spiral groove. The micron spiral groove is arranged on the inner wall of the elastic tube body, so that the liquid conductive slurry is bound by capillary force when the elastic tube body is stretched, and the liquid conductive slurry is continuously distributed in the inner cavity. The application realizes the uniform and continuous distribution of the conductive slurry in the process of super large stretching deformation of the wire harness, avoids the conductive failure caused by local aggregation or flow break of the slurry, and makes the wire harness maintain stable conductive performance under repeated deformation working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductive wire harness technology, and in particular to a conductive wire harness and its preparation method. Background Technology

[0002] Flexible wire harnesses are core components in industrial robotic arms, collaborative robots, humanoid robots, medical surgical robots, dexterous hands, and dynamic mechanisms of new energy vehicles, carrying power supply, servo control, encoder feedback, and transmission of visual and force sensing signals. As these devices develop towards higher degrees of freedom, higher precision, and higher reliability, their joints and moving parts need to withstand long-term high-frequency reciprocating bending, three-dimensional torsion, tensile friction, and continuous vibration. This places extremely stringent requirements on the flexibility, fatigue resistance, and environmental adaptability of wire harnesses.

[0003] Currently, flexible wiring harnesses widely used in industrial and automotive fields still primarily use traditional copper conductors. The conductors of flexible cables typically employ a multi-strand ultra-fine tinned copper wire stranded structure, improving bending and torsional resistance by reducing the diameter of individual wires (≤0.08mm) and using a small twist pitch design. However, this structure still presents the following problems in practical use: 1. Copper wire fatigue fracture: In applications such as car door hinges, robotic arm joints, and seat adjustment mechanisms, which require repeated stretching, torsion, and vibration, copper conductors are highly susceptible to core wire fatigue fracture, sheath cracking, shielding failure, and signal packet loss, significantly increasing equipment downtime and maintenance costs. 2. Difficulty in processing fine-diameter wires: The application of fine-square-gauge conductors faces challenges such as easy wire breakage during stripping and crimping, resulting in low production efficiency and high defect rates. 3. Difficulty in balancing flexibility and current carrying capacity: To improve the flexibility of traditional copper conductors, the number of individual wires must be increased and the diameter reduced, but this reduces the conductor's current carrying capacity and mechanical strength, creating an inherent contradiction.

[0004] To address the aforementioned issues, researchers have recently begun exploring flexible wire solutions that use liquid metals instead of traditional solid metals as the conductive medium. Liquid metals are liquid at room temperature, possessing both the high conductivity of metals and the deformability of fluids. Encapsulating them within elastic tubes or substrates can yield flexible wires with exceptional tensile strength and fatigue resistance. Existing technologies include reports of preparing stretchable wires by injecting gallium indium tin alloys into thermoplastic elastomer tubes, and methods using negative pressure to infuse liquid metal into silicone tubes to prepare flexible wires.

[0005] However, existing liquid metal flexible wire technology still has the following shortcomings:

[0006] 1. Liquid metal lacks an effective restraint mechanism within the elastic tube. Under conditions of ultra-large tensile deformation (such as strain exceeding 500%), liquid metal is prone to uneven distribution or even localized flow interruption within the tube, leading to a sharp increase in resistance or even a circuit break, thus limiting the stretchable range of the conductor.

[0007] 2. Limited operating temperature range. Most existing liquid metal wires use gallium indium alloys or gallium indium tin alloys without composition optimization. They are prone to solidification and freezing at low temperatures, and solvents or low-boiling-point components are prone to volatilization at high temperatures. They are difficult to operate stably in a wide temperature range of -40℃ to 150℃, and cannot meet the use requirements of harsh environments such as automotive and industrial equipment.

[0008] 3. There is a lack of reliable solutions for the connection and sealing of liquid metal conductors to external terminals. Liquid metal has high surface tension and fluidity, making traditional terminal connection methods such as crimping and welding unsuitable. How to achieve reliable electrical conduction between liquid metal and terminals while ensuring long-term sealing and leak prevention at the connection is a technical problem that urgently needs to be solved.

[0009] 4. Difficulty in multi-channel integration. In scenarios requiring parallel routing of multiple conductors, existing liquid metal conductors are mostly single, independent structures, lacking effective multi-channel integration solutions. Summary of the Invention

[0010] To address the aforementioned technical problems, this invention proposes a flexible liquid-based conductive wire harness and its preparation method, which solves the problems of internal conductive medium interruption failure and liquid leakage at terminal connections in existing liquid metal wire harnesses under high tensile conditions.

[0011] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0012] A flexible liquid-based conductive wire harness includes an elastic tube and a liquid conductive slurry filled within the elastic tube. Terminals are located at both ends of the elastic tube, and these terminals are electrically connected to the liquid conductive slurry. The inner wall of the elastic tube has micron-level spiral grooves, which are used to bind the liquid conductive slurry through capillary force when the elastic tube is stretched, ensuring a continuous distribution of the liquid conductive slurry within the inner cavity. This invention, by providing micron-level spiral grooves on the inner wall of the elastic tube, enables the liquid conductive slurry to be bound by capillary force during stretching, maintaining a continuous distribution of the liquid conductive slurry within the inner cavity. This achieves a uniform and continuous distribution of the conductive slurry during ultra-large tensile deformation of the wire harness, avoiding conductive failure caused by localized slurry aggregation or flow interruption, and ensuring stable conductivity of the wire harness under repeated deformation conditions.

[0013] Furthermore, in order to ensure a stable and reliable electrical connection between the terminal and the liquid conductive slurry, and to achieve a firm fixation and long-term sealing and leak-proof connection at the connection between the terminal and the elastic tube, a conductive pin is provided at the tail of the terminal. The conductive pin is inserted into the inner cavity of the elastic tube and wetted and contacts the liquid conductive slurry to achieve electrical connection. The tail of the terminal and the end of the elastic tube are fixedly connected by a clamp. A potting adhesive layer is provided at the connection between the clamp and the elastic tube to seal the end of the elastic tube.

[0014] Furthermore, in order to achieve large tensile deformation while ensuring the flexibility of the elastic tube body and to ensure the binding effect of the capillary grooves on the liquid conductive slurry, the elastic tube body is a silicone tube with an inner diameter of 0.5mm to 10mm, a wall thickness of 0.3mm to 2.0mm, a depth of 10μm to 200μm, a width of 20μm to 300μm, a pitch of 0.5mm to 5mm, and a cross-sectional shape of the micron-level spiral grooves of V-shape, U-shape, semi-circle, or trapezoidal.

[0015] Furthermore, the liquid conductive paste is a gallium-indium-tin ternary liquid metal alloy with an alloy ratio of Ga 68.5wt%, In 21.5wt%, and Sn 10wt%; or the liquid conductive paste is a modified MXene high-conductivity organic paste, wherein the modified MXene is alkylated Ti3C2T. x MXene is dispersed in organic solvent systems resistant to high and low temperatures.

[0016] Furthermore, to address the issues of existing liquid metal conductors' tendency to solidify and freeze at low temperatures and volatilize and fail at high temperatures, and to adapt to wide temperature range requirements from -40℃ to 150℃, a two-phase conductive pathway consisting of an "MXene two-dimensional network + liquid metal continuous liquid phase" is constructed. Through the synergistic cooperation of its components, stable operation and high-efficiency conductivity over a wide temperature range are achieved. The liquid conductive paste is a gallium indium tin-MXene two-phase composite liquid conductive paste, including alkylated modified Ti3C2T. x The composition consists of MXene nanosheets with a mass fraction of 2.0%–5.0%, micron-sized gallium indium tin liquid metal droplets with a mass fraction of 10.0%–20.0%, nano-silver wetting agent with a mass fraction of 0.2%–1.0%, halogen-free thermally conductive and flame-retardant composite filler with a mass fraction of 4.0%–8.0%, and the balance being a high-boiling-point, low-temperature resistant composite organic solvent.

[0017] Furthermore, to further define the optimal parameter range of each component in the two-phase composite slurry and ensure the coordinated combination of each component in the formulation system, the alloy ratio of the gallium indium tin liquid metal microdroplets is Ga 68.5wt%, In 21.5wt%, Sn 10wt%, and the particle size of the gallium indium tin liquid metal microdroplets is 2μm~15μm, with alkylated modified Ti3C2T xThe MXene nanosheets have a transverse dimension of 0.3μm to 2μm and a thickness of 1nm to 5nm. The nano-silver wetting agent consists of spherical nano-silver particles with a particle size of 20nm to 80nm. The halogen-free thermally conductive and flame-retardant composite filler is a composite system of hexagonal boron nitride powder and ultrafine aluminum hydroxide powder, with a mass ratio of hexagonal boron nitride to ultrafine aluminum hydroxide of 1:1.5 to 1:3.

[0018] Furthermore, in order to achieve integrated wiring for parallel transmission of multi-channel signals, the elastic tube is provided with multiple tubes, which are arranged in a regular manner, covered with an elastic encapsulation layer on the outside and integrally formed into an integrated tube bundle, with each elastic tube forming an independent conductive channel.

[0019] This invention provides a method for preparing a flexible liquid-based conductive wire harness, comprising the following steps:

[0020] S1. Slurry pretreatment: The liquid conductive slurry is placed in a vacuum degassing device to remove air bubbles from the slurry.

[0021] S2, Slurry injection: Seal one end of the elastic tube and connect the other end to a vacuum injection device to inject the degassed liquid conductive slurry into the inner cavity of the elastic tube under negative pressure;

[0022] S3. Clamp connection: Insert the tail of the terminal into the end of the elastic tube, and fit a clamp on the end of the elastic tube. After positioning, clamp and fix it.

[0023] S4. Sealing with adhesive: Injecting sealant at the connection between the clamp and the elastic tube body, and curing to form a sealing layer;

[0024] S5. Reliability Testing: The assembled wire harness undergoes high and low temperature cyclic aging tests, reciprocating tensile fatigue tests, conduction resistance stability tests, and sealing leakage tests. The above-mentioned preparation method of this invention ensures that the liquid conductive slurry fills the elastic tube cavity densely without air gaps through vacuum degassing and negative pressure injection. Combined with the integrated assembly process of clamp fixing and glue sealing, it achieves high-efficiency and high-yield preparation of the wire harness.

[0025] Furthermore, in order to ensure that the liquid conductive slurry completely fills the micron-level spiral grooves without any air bubbles while ensuring injection efficiency, in step S2, the vacuum degree of vacuum injection is -0.08MPa to -0.1MPa, the injection speed is 10 to 80 mm / min, and the injection temperature is 20℃ to 40℃.

[0026] Furthermore, in order to ensure a reliable seal between the potting compound layer and the connection between the clamp and the elastic tube, and to achieve a long-term leak-proof effect, in step S4, the sealant is a two-component flexible polyurethane potting compound, the potting pressure is 0.12MPa~0.2MPa, the pressure is maintained for 30s after potting, and the curing process is to pre-cure at 60℃ for 60min and then heat to 80℃ for 120min.

[0027] The beneficial effects of this invention are:

[0028] 1. This invention creates micron-level spiral grooves on the inner wall of an elastic tube, using the capillary force of the grooves to bind the liquid conductive slurry. This ensures that the liquid conductive slurry is continuously distributed along the inner cavity during the ultra-large tensile deformation of the wire bundle, avoiding conductive failure caused by local accumulation or interruption of the slurry, and achieving stable conductivity within the strain range of 0 to 700%.

[0029] 2. This invention creates micron-level spiral grooves on the inner wall of the elastic tube, forming a continuous capillary binding effect on the liquid conductive slurry during the stretching process. This keeps the resistance change rate before and after stretching within 5%, ensuring the signal transmission stability and electrical reliability of the wire harness under repeated deformation conditions.

[0030] 3. This invention uses liquid conductive paste as the conductive medium, combined with an elastic tube, so that the wire harness does not have the problem of metal fatigue fracture under repeated bending, stretching and torsion conditions. It fundamentally solves the problem of signal interruption and equipment downtime caused by copper wire fatigue fracture in dynamic mechanisms of traditional copper wire harnesses, and greatly extends the service life of the wire harness.

[0031] 4. This invention achieves reliable electrical conduction between the liquid conductive medium and the external terminal by setting a conductive pin at the tail of the terminal and inserting it into the inner cavity of the elastic tube to wet and contact with the liquid conductive slurry. At the same time, the dual protective structure of clamp locking and sealing with potting adhesive layer effectively prevents the liquid conductive slurry from leaking from the connection and improves the safety of the wire harness.

[0032] 5. This invention uses gallium indium tin ternary liquid metal alloy, modified MXene high-conductivity organic paste, or gallium indium tin-MXene dual-phase composite liquid conductive paste as the conductive medium, combined with a high and low temperature resistant silicone elastic tube, so that the wire harness can work stably in a wide temperature range of -40℃ to 150℃, without solidifying or becoming brittle at low temperatures and without volatilizing or leaking at high temperatures, meeting the usage requirements of harsh environments such as automotive and industrial equipment.

[0033] 6. This invention integrates multiple hollow silicone microtubes into a bundle by neatly arranging them and covering them with an elastic encapsulation layer. Each microtube independently forms a closed conductive channel, realizing integrated wiring for parallel transmission of multi-channel signals and solving the technical problem of multi-channel integration of existing liquid metal wires.

[0034] 7. This invention abandons the traditional processing techniques of stripping and crimping copper wire harnesses, and adopts an assembly method of slurry injection, clamp connection and glue sealing, which avoids the problem of wire breakage in the stripping and crimping process of fine wire diameter wires, and improves production efficiency and product qualification rate.

[0035] 8. The wiring harness of the present invention has the advantages of being lightweight, highly flexible, fatigue-resistant, and vibration-resistant. It is suitable for applications involving high-frequency bending, reciprocating deformation, and strong vibration, such as wiring of dynamic mechanisms in new energy vehicles, flexible connections inside power batteries, industrial collaborative robots, humanoid soft robots, rehabilitation exoskeletons, and wearable sensing devices. It has extremely high commercial application value. Attached Figure Description

[0036] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0037] Figure 1 This is a three-dimensional structural diagram of the present invention.

[0038] Figure 2 This is a front view structural diagram of the present invention.

[0039] Figure 3 This is a schematic diagram of the structure of the elastic tube of the present invention. Detailed Implementation

[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0041] The flexible liquid-based conductive wire harness described in Embodiment 1 of the present invention, such as Figure 1 and Figure 2 As shown, it includes an elastic tube 1, a liquid conductive slurry 2 filled into the inner cavity of the elastic tube 1, and a pair of terminals 3 respectively disposed at both ends of the elastic tube 1.

[0042] like Figure 3As shown, the inner wall surface of the elastic tube 1 is machined with micron-sized spiral grooves 4, with cross-sectional shapes of V-shape, U-shape, semi-circular shape, or trapezoidal shape. The grooves extend spirally along the inner wall of the elastic tube 1. The micron-sized spiral grooves 4 are formed by femtosecond laser processing and extend spirally from one end to the other along the inner wall of the elastic tube 1. When the elastic tube 1 is stretched axially, the volume and shape of the inner cavity change. During the flow process, the liquid conductive slurry 2 is bound by the capillary force of the micron-sized spiral grooves 4, so that the liquid conductive slurry 2 is continuously distributed along the inner cavity throughout the stretching process and will not cause local aggregation or flow interruption due to gravity or uneven surface tension.

[0043] like Figure 1 As shown, the head of terminal 3 has a conventional terminal block structure for connecting external wires or equipment. The tail of terminal 3 has an integrally formed conductive pin 31. The conductive pin 31 is cylindrical, made of brass, and gold-plated. When connecting terminal 3, the conductive pin 31 is inserted into the inner cavity from the end of the elastic tube 1, with an interference fit between the outer wall of the conductive pin 31 and the inner wall of the elastic tube 1. After insertion, the front end of the conductive pin 31 is completely immersed in the liquid conductive slurry 2, and the surface of the conductive pin 31 is in contact with the liquid conductive slurry 2, achieving electrical conductivity.

[0044] like Figure 1 and Figure 2 As shown, the tail of terminal 3 is fixedly connected to the end of elastic tube 1 by clamp 5. Clamp 5 is a split flexible clamp. Clamp 5 is sleeved on the outside of the end of elastic tube 1, corresponding to the overlapping area between the tail of terminal 3 and elastic tube 1. Clamp 5 is tightened by bolts, so that clamp 5 tightly presses the end of elastic tube 1 against the outer wall of the tail of terminal 3, thereby achieving fixation.

[0045] A potting compound layer is provided at the connection between the clamp 5 and the elastic tube 1. In this embodiment, the potting compound layer is formed by curing a two-component flexible polyurethane potting compound. The potting compound layer covers the joint gap between the clamp 5 and the elastic tube 1, and fills the inner gap of the clamp 5 and the groove at the tail of the terminal 3, completely sealing the interface between the tail of the terminal 3 and the end of the elastic tube 1, preventing the liquid conductive slurry 2 from leaking from the connection.

[0046] In one specific embodiment, the elastic tube 1 is a silicone flexible tube made of methyl vinyl silicone rubber with a Shore A hardness of 50A. The inner diameter of the elastic tube 1 is 3mm, the wall thickness is 1.0mm, and the length is 200mm. The micron-level spiral groove 4 has a depth of 100μm, a width of 150μm, a pitch of 2.5mm, and a V-shaped cross-section.

[0047] Liquid conductive paste 2 is a gallium indium tin-MXene dual-phase composite liquid conductive paste. In this embodiment, based on 100% of the total mass, the mass fraction of each component is as follows: alkylated modified Ti3C2T x The composition of the Ti3C2T alloy is as follows: MXene nanosheets (3.5%), micron-sized gallium indium tin liquid metal droplets (15.0%), spherical nano-silver wetting agent (0.6%), halogen-free thermally conductive and flame-retardant composite filler (6.0%), and high-boiling-point, low-temperature resistant composite with organic solvent as the balance (74.9%). The alloy ratio of the gallium indium tin liquid metal droplets is Ga 68.5 wt%, In 21.5 wt%, and Sn 10 wt%, with a droplet size of 8 μm. Alkylation modification of Ti3C2T x The MXene nanosheets have a lateral dimension of 1.2 μm and a thickness of 3 nm. Alkylation-modified Ti3C2T x The preparation method of MXene nanosheets is as follows: Ti3C2T x MXene nanosheets were dispersed in anhydrous ethanol and ultrasonically dispersed for 20 min. Octadecyltrimethoxysilane was added at a mass ratio of 1:1 to MXene. The mixture was stirred at 70 °C for 8 h. After the reaction, the nanosheets were centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 60 °C for 18 h to obtain alkylated modified MXene nanosheets. The spherical silver nanoparticles had a particle size of 50 nm. The halogen-free, thermally conductive, and flame-retardant composite filler was a mixture of hexagonal boron nitride powder and ultrafine aluminum hydroxide powder at a mass ratio of 1:2. The high-boiling-point, low-temperature resistant composite was a mixture of a high-boiling-point alcohol ether solvent and a low-boiling-point environmentally friendly ester solvent at a mass ratio of 8:2.

[0048] Example 2 has the same overall structure as Example 1, except that the micron-level spiral groove 4 is formed by micro-nano imprinting on the inner wall of the mold.

[0049] Furthermore, the liquid conductive paste 2 is a gallium indium tin-MXene two-phase composite liquid conductive paste. Based on 100% total mass, the mass fraction of each component is: alkylated modified Ti3C2T x The composition consists of 2.0% MXene nanosheets, 10.0% micron-sized gallium indium tin liquid metal droplets, 0.2% spherical nano-silver wetting agent, 4.0% halogen-free thermally conductive and flame-retardant composite filler, and the balance (83.8%) of the high-boiling-point, low-temperature resistant composite with organic solvent. The gallium indium tin liquid metal droplets have a particle size of 2 μm, and the alkylated modified Ti3C2T... x The MXene nanosheets have a transverse dimension of 0.3 μm and a thickness of 1 nm, the spherical silver nanoparticles have a particle size of 20 nm, the mass ratio of hexagonal boron nitride to ultrafine aluminum hydroxide is 1:1.5, and the mass ratio of high-boiling-point alcohol ether solvent to low-boiling-point environmentally friendly ester solvent is 7:3.

[0050] Example 3 provides a single-core flexible liquid-based conductive wire harness, whose overall structure is the same as that of Example 1, except that the liquid conductive paste 2 is a gallium indium tin-MXene dual-phase composite liquid conductive paste. Based on 100% of the total mass, the mass fraction of each component is: alkylated modified Ti3C2T x The composition consists of 5.0% MXene nanosheets, 20.0% micron-sized gallium indium tin liquid metal droplets, 1.0% spherical nano-silver wetting agent, 8.0% halogen-free thermally conductive and flame-retardant composite filler, and the balance (66.0%) of the high-boiling-point, low-temperature resistant composite with organic solvent. The gallium indium tin liquid metal droplets have a particle size of 15 μm, and the alkylated modified Ti3C2T... x The MXene nanosheets have a transverse dimension of 2 μm and a thickness of 5 nm, the spherical silver nanoparticles have a particle size of 80 nm, the mass ratio of hexagonal boron nitride to ultrafine aluminum hydroxide is 1:3, and the mass ratio of high-boiling-point alcohol ether solvent to low-boiling-point environmentally friendly ester solvent is 8.5:1.5.

[0051] Example 4: This example provides a multi-core integrated tubular flexible liquid-based conductive wire harness. It includes multiple elastic tubes 1; in this example, seven tubes are used. The seven elastic tubes 1 are arranged in parallel and regular pattern, with one located at the center and the other six arranged in a hexagonal pattern around the center. The elastic tubes 1 are parallel to each other and evenly spaced.

[0052] Each elastic tube 1 is a silicone flexible tube. The inner wall surface of each elastic tube 1 is machined with micron-level spiral grooves 4.

[0053] Each elastic tube 1 has a cavity filled with liquid conductive paste 2. The liquid conductive paste 2 is a gallium indium tin-MXene two-phase composite liquid conductive paste, and its formula composition, component mass fraction, alloy ratio and component parameters are the same as those in Example 1.

[0054] The seven elastic tubes 1 are collectively covered by an elastic encapsulation layer. The elastic encapsulation layer is made of silicone. The elastic encapsulation layer is applied to the outside of the seven elastic tubes 1 by injection molding or dip coating, thus molding the seven elastic tubes 1 into an integrated tube bundle.

[0055] Each elastic tube 1 has a terminal 3 at both ends, and the tail of the terminal 3 has a conductive pin 31. The conductive pin 31 is inserted into the inner cavity of the corresponding elastic tube 1 and is wetted and in contact with the liquid conductive paste 2. Each elastic tube 1 independently forms a closed three-dimensional conductive channel, and adjacent channels are electrically insulated and isolated by an elastic encapsulation layer. The terminals 3 are arranged in a predetermined pattern at the ends of the integrated tube bundle to facilitate mating with external multi-core connectors.

[0056] Each end of the elastic tube 1 is fixedly connected to the corresponding terminal 3 by an independent clamp 5, and a potting compound layer is provided at the connection of the clamp 5 for sealing.

[0057] As a parallel arrangement in this embodiment, the number of elastic tubes 1 can also be three, four, six, twelve, nineteen, or other quantities. The arrangement of each elastic tube 1 can also be adjusted according to actual needs, such as a straight line arrangement, a rectangular arrangement, or a ring arrangement. The dimensions of each elastic tube 1 can be the same or different.

[0058] Example 5: This example provides a flexible liquid-based conductive wire harness using gallium indium tin liquid metal paste as the conductive medium.

[0059] Its overall structure is the same as that of Example 1.

[0060] The conductive phase used in the liquid conductive paste 2 is a gallium-indium-tin ternary alloy, with an alloy composition of 68.5 wt% Ga, 21.5 wt% In, and 10 wt% Sn. This ternary alloy has an equilibrium melting temperature of approximately 11 °C and exhibits significant supercooling characteristics. In a high-purity, clean system, its solidification temperature can be as low as -19 °C. Under high-purity, undisturbed conditions, it can maintain a liquid state for a short period at -40 °C due to kinetic supercooling. This state is metastable and prone to heterogeneous nucleation and solidification under mechanical vibration, thermal shock, or the induction of solid impurities. Within the operating temperature range of 150 °C, the alloy phase is stable and does not undergo thermal decomposition. The vapor pressures of each component are extremely low, and it can be approximated as having no elemental volatilization.

[0061] The preparation method is as follows: weigh high-purity (≥99.99%) gallium, indium, and tin raw materials according to the above mass ratio, place them in a vacuum melting furnace, and ensure the vacuum degree is ≤1×10⁻⁶. -3 Pa, heated to 170℃, kept warm and stirred for 45 minutes to fully melt and alloy the three metals, and then naturally cooled to room temperature to obtain gallium indium tin ternary liquid metal alloy slurry.

[0062] Furthermore, the structure and connection method of terminal 3, clamp 5 and potting compound layer are the same as in Example 1.

[0063] As a parallel option in this embodiment, the ratio of the gallium indium tin ternary liquid metal alloy can also be other eutectic or near-eutectic ratios, such as Ga 61wt%, In 29wt%, Sn 10wt%. As long as it can achieve non-freezing at -40℃ and non-volatilization at 150℃, it can be used as the conductive medium of the present invention.

[0064] Example 6: This example provides a flexible liquid-based conductive wire harness using modified MXene highly conductive organic slurry as the conductive medium.

[0065] Liquid conductive paste 2 is a modified MXene highly conductive organic paste. The modified MXene is alkylated Ti3C2T. x MXene is dispersed in a high-boiling-point, low-temperature resistant compound organic solvent. The mass fraction of alkylated modified MXene nanosheets in the slurry is 3.0%–5.0%. The slurry also contains auxiliary conductive agents (such as conductive carbon black or carbon nanotubes), with the amount of auxiliary conductive agents ranging from 5% to 20% of the mass of MXene.

[0066] The preparation method of the slurry is as follows: alkylated modified Ti3C2T x MXene nanosheets were dispersed in a high-boiling-point, low-temperature resistant compound organic solvent and ultrasonically dispersed for 20 min. Conductive carbon black was added as an auxiliary conductive agent. The mixture was then ground and dispersed 4–6 times in a three-roll mill until the slurry fineness was ≤10 μm. Vacuum degassing was performed for 15 min to obtain a modified MXene highly conductive organic slurry. This slurry did not freeze at -40℃ and showed no solvent evaporation or powder decomposition failure at 150℃.

[0067] Furthermore, the structure and connection method of terminal 3, clamp 5 and potting compound layer are the same as in Example 1.

[0068] Example 7: This example provides a flexible liquid-based conductive wire harness using a non-silicone elastic tube. As a parallel embodiment of the present invention, the elastic tube 1 can also be made of other elastic insulating materials.

[0069] In one embodiment, the elastic tube 1 is a thermoplastic polyurethane elastomer tube with a Shore hardness of 60A to 80A. Its low-temperature resistance is better than that of ordinary polyurethane materials, and it can maintain its elasticity in an environment of -40℃.

[0070] In another embodiment, the elastic tube 1 is made of fluorosilicone rubber, which has better high-temperature resistance than ordinary silicone rubber and can be used for a long time in an environment of 200°C.

[0071] In another embodiment, the elastic tube 1 is an EPDM rubber tube, which has good aging resistance and electrical insulation properties.

[0072] The inner walls of the elastic tubes 1 made of different materials are all machined with micron-level spiral grooves 4, and liquid conductive slurry 2 is poured into the inner cavity. Terminals 3 are set at both ends, and they are connected and sealed by clamps 5 and potting adhesive layers. The specific structure and working principle of each scheme are the same as those of the aforementioned embodiments.

[0073] Example 8: This example provides a parallel arrangement of capillary grooves with different cross-sectional shapes.

[0074] The cross-sectional shape of the micron-scale spiral groove 4 is not limited to the V-shape, U-shape, semi-circle, or trapezoidal shape in the aforementioned embodiments.

[0075] In one design, the cross-sectional shape of the micron-scale helical groove 4 is rectangular, meaning the bottom of the groove is flat and the sidewalls are perpendicular to the bottom. The depth of the rectangular groove is 50μm to 150μm, and the width is 50μm to 200μm. The rectangular groove can be formed layer by layer by femtosecond laser scanning during processing, making the process control relatively simple.

[0076] In another design, the cross-sectional shape of the micron-scale spiral groove 4 is triangular, meaning the bottom of the groove is a pointed tip. The depth of the triangular groove is 10μm to 100μm, and the width is 20μm to 100μm. The pointed tip shape of the triangular groove is more conducive to generating a local capillary force concentration effect, resulting in a more significant binding effect on the liquid conductive paste 2.

[0077] In another design, the cross-sectional shape of the micron-scale spiral trench 4 is arc-shaped, meaning the bottom and sidewalls of the trench transition into an arc. The depth of the arc-shaped trench is 20μm to 150μm, and the width is 30μm to 200μm. The arc-shaped trench has no sharp corners, which facilitates the smooth flow of the liquid conductive paste 2 within the trench and reduces stress concentration.

[0078] The micron-level spiral grooves 4 with different cross-sectional shapes described above can all achieve the function of binding liquid conductive paste 2 by capillary force. Technicians can select the appropriate cross-sectional shape according to specific processing conditions and performance requirements.

[0079] Example 9: This example provides a parallel arrangement of capillary grooves with different spiral directions.

[0080] There are multiple possible spiral directions for the micron-level spiral groove 4.

[0081] In one embodiment, the micron-level spiral groove 4 is a left-handed spiral, meaning that the groove extends in a left-handed direction along the inner wall of the elastic tube 1.

[0082] In another scheme, the micron-level spiral groove 4 is a right-handed spiral, that is, the groove extends in a right-handed direction along the inner wall of the elastic tube 1.

[0083] In another design, the micron-level spiral groove 4 is a double-helix structure, meaning that two spiral grooves are simultaneously machined on the inner wall of the elastic tube 1. The spiral directions of the two grooves can be the same or opposite, and the two grooves are staggered in the axial direction. The double-helix structure can form a denser capillary force distribution on the inner wall of the elastic tube 1, further improving the binding effect on the liquid conductive paste 2.

[0084] Example 10

[0085] This embodiment provides a method for preparing a flexible liquid-based conductive wire harness, which is used to prepare a single-core flexible liquid-based conductive wire harness as described in Example 1.

[0086] S1. Pretreatment of Liquid Conductive Slurry: A gallium indium tin-MXene biphase composite liquid conductive slurry was selected and prepared according to the formula in Example 1. The slurry was then placed in a vacuum degassing device. The vacuum degree of the degassing device was -0.095 MPa, the degassing temperature was 25°C, and the degassing time was 20 min. The degassing process removed air bubbles from the slurry until no obvious air bubbles were observed escaping from the slurry surface. After degassing, the slurry was transferred to the feed cylinder of the injection equipment for later use.

[0087] S2. Slurry Injection: Take a silicone tube as the elastic tube 1. The inner diameter of the elastic tube 1 is 3mm, the wall thickness is 1.0mm, and the length is 200mm. Its inner wall has been pre-processed with micron-level spiral grooves 4. Seal one end of the elastic tube 1 with a temporary sealing head, and connect the other end to the injection head of the vacuum injection equipment. Start the vacuum pump to put the inner cavity of the elastic tube 1 into a negative pressure state with a vacuum degree of -0.09MPa. Open the valve of the injection head, so that the degassed liquid conductive slurry 2 is drawn into the inner cavity from the open end of the elastic tube 1 under the action of negative pressure until the slurry completely fills the entire inner cavity and reaches the sealed end of the elastic tube 1. The injection time is 15 minutes, and the injection temperature is 25℃. After the injection is completed, remove the temporary sealing head and wipe the excess slurry overflowing from the openings at both ends of the elastic tube 1 with a clean cloth.

[0088] S3. Clamp Connection: Insert the conductive pin 31 at the tail of terminal 3 into the inner cavity of the elastic tube 1 from the end to a depth of 12mm. The diameter of the conductive pin 31 is 2.4mm, forming an interference fit of 0.15mm with the inner diameter of the elastic tube 1 (3mm). A clamp 5 is fitted onto the outer side of the end of the elastic tube 1, aligned with the overlapping area between the tail of terminal 3 and the elastic tube 1. After positioning, fasten the clamp 5 to tightly press the end of the elastic tube 1 against the outer wall of the tail of terminal 3. The other end of the elastic tube 1 is connected to the second terminal 3 in the same manner.

[0089] S4. Sealing with Glue: Glue is applied to the connection between clamp 5 and elastic tube 1. A two-component flexible polyurethane potting compound with a Shore A hardness of 50A is used. Before gluing, a silicone plug is used to protect the insertion end of terminal 3 to prevent glue contamination of the mating parts. Oil and dust on the surfaces of elastic tube 1 and clamp 5 are wiped with anhydrous ethanol. The wire harness with crimped terminal 3 is placed in the split-type mold for fixation. The gluing equipment is started, and the gluing pressure is controlled at 0.16MPa. A slow, ultra-low-pressure gluing method is used, injecting the sealant from the interface between clamp 5 and elastic tube 1 until a continuous flow of bubble-free glue from the vent hole is observed. The gluing is stopped immediately. After gluing, the pressure is maintained for 30 seconds, allowing the glue to flow under its own weight and the maintaining pressure to fill the gap in clamp 5, the inner gap of clamp 5, and the groove at the tail of terminal 3. The wire harness, along with the mold, is filled with sealant and placed in an oven for segmented curing: first, pre-curing is performed in an oven at 60℃ for 60 minutes, then the oven temperature is increased to 80℃ and curing continues for 120 minutes. After curing, the mold is removed and allowed to cool naturally to room temperature. After demolding, the flash at the sealant injection port is trimmed with a knife.

[0090] S5. Reliability Testing: The assembled wire harness undergoes the following tests sequentially: High and Low Temperature Cyclic Aging Test – The wire harness is placed in a high and low temperature test chamber and cycled 10 times between -40℃ and 150℃, with each temperature point held for 2 hours. The wire harness is then inspected for cracks or deformation. Reciprocating Tensile Fatigue Test – The wire harness is mounted on a universal tensile testing machine and subjected to 1000 reciprocating stretches at a tensile speed of 100mm / min within a strain range of 0–500%. The wire harness is then inspected for breaks or leakage. Conductivity Stability Test: The DC resistance of the wire harness before and after stretching is measured using the four-probe method, and the rate of change in resistance is calculated. Sealing and Leakage Test: Dust-free white filter paper is tightly bonded to the end sealing area of ​​the wire harness and kept in contact for 30 minutes. The wire harness sealing layer is visually inspected for cracks, bubbles, holes, and interface peeling. The filter paper surface is free of oil stains and colored spots.

[0091] Example 11

[0092] This embodiment provides a method for preparing a flexible liquid-based conductive wire harness, which is used to prepare a single-core flexible liquid-based conductive wire harness as described in Example 2, wherein the process parameters of each step are taken at the lower limit value.

[0093] S1. Pretreatment of liquid conductive paste: Prepare gallium indium tin-MXene biphase composite liquid conductive paste according to the formula in Example 2, and place it in a vacuum degassing device. The vacuum degree is -0.08MPa, the degassing temperature is 20℃, and the degassing time is 10min.

[0094] S2. Slurry Injection: Take an elastic tube 1 with an inner diameter of 0.5 mm, a wall thickness of 0.3 mm, and a length of 100 mm. The inner wall of the tube has been pre-machined with micron-level spiral grooves 4. Seal one end of the elastic tube 1 and connect the other end to a vacuum injection device. The vacuum degree is -0.08 MPa, the injection time is 5 min, and the injection temperature is 20℃.

[0095] S3. Clamp Connection: Insert the conductive pin 31 (0.4mm in diameter, i.e., 80% of the inner diameter of the elastic tube 1) into the inner cavity of the elastic tube 1 to a depth of 5mm. Place the clamp 5, which is 3mm wide and 0.5mm thick, on the outer side of the end of the elastic tube 1, with a locking torque of 0.5N·m.

[0096] S4. Encapsulation: Use a two-component flexible polyurethane potting compound with a Shore A hardness of 40A. Control the potting pressure at 0.12 MPa, and maintain pressure for 30 seconds after a continuous flow of bubble-free compound from the vent hole. The curing process is as follows: pre-cur at 60℃ for 60 minutes, then cure at 80℃ for 120 minutes.

[0097] S5. Reliability testing: Same as in Example 10.

[0098] Example 12

[0099] A method for preparing a flexible liquid-based conductive wire harness, used to prepare a single-core flexible liquid-based conductive wire harness as described in Example 3.

[0100] S1. Pretreatment of liquid conductive paste: Prepare gallium indium tin-MXene biphase composite liquid conductive paste according to the formula in Example 3, and place it in a vacuum degassing device. The vacuum degree is -0.1MPa, the degassing temperature is 40℃, and the degassing time is 30min.

[0101] S2. Slurry Injection: Take an elastic tube 1 with an inner diameter of 10mm, a wall thickness of 2.0mm, and a length of 500mm. The inner wall of the tube has been pre-machined with micron-level spiral grooves 4. Seal one end of the elastic tube 1 and connect the other end to a vacuum injection device. The vacuum degree is -0.1MPa, the injection time is 30min, and the injection temperature is 40℃.

[0102] S3. Clamp Connection: Insert the conductive pin 31 (8mm in diameter, i.e., 80% of the inner diameter of the elastic tube 1) into the inner cavity of the elastic tube 1 to a depth of 20mm. Place the clamp 5, which is 10mm wide and 2.0mm thick, on the outer side of the end of the elastic tube 1, with a locking torque of 3.0N·m.

[0103] S4. Encapsulation: Use a two-component flexible polyurethane potting compound with a Shore A hardness of 60A. Control the potting pressure at 0.2 MPa, and maintain pressure for 30 seconds after a continuous flow of bubble-free compound from the vent hole. The curing process is as follows: pre-cur at 60℃ for 60 minutes, then cure at 80℃ for 120 minutes.

[0104] S5. Reliability testing: Same as in Example 10.

[0105] Example 13

[0106] A method for preparing a multi-core integrated tubular flexible liquid-based conductive wire harness, used to prepare the multi-core integrated tubular wire harness as described in Example 4.

[0107] S1. Pretreatment of liquid conductive paste: Prepare gallium indium tin-MXene biphase composite liquid conductive paste according to the formula in Example 1, and place it in a vacuum degassing device. The vacuum degree is -0.095MPa, the degassing temperature is 25℃, and the degassing time is 20min.

[0108] S2. Slurry Injection: Take seven elastic tubes 1, each with an inner diameter of 2mm, a wall thickness of 0.8mm, and a length of 300mm. The inner wall of each elastic tube 1 is pre-machined with micron-level spiral grooves 4. Arrange the seven elastic tubes 1 in parallel and orderly fashion (one at the center, and six arranged in a hexagonal pattern around the center), temporarily fix them with clamps, and then place them as a whole into the vacuum injection equipment. Connect one end of each elastic tube 1 to the corresponding injection head, and seal the other end. Start the vacuum pump to bring the inner cavity of each elastic tube 1 into a negative pressure state, with a vacuum degree of -0.09MPa. Open the valves of each injection head to simultaneously inject the degassed liquid conductive slurry 2 into the inner cavity of the seven elastic tubes 1. The injection time is 15 minutes, and the injection temperature is 25℃.

[0109] S3. Tube Bundle Forming: After the infusion is completed, an elastic encapsulation layer is wrapped around the outside of the seven elastic tubes 1. The elastic encapsulation layer is made of silicone and is wrapped around the outside of the seven elastic tubes 1 by injection molding. The injection molding temperature is 120℃ and the curing time is 20min, forming an integrated elastic encapsulation layer with a thickness of 1.5mm, which fixes the seven elastic tubes 1 into an integrated tube bundle.

[0110] S4. Clamp connection and glue sealing: Connect the two ends of each elastic tube 1 to the terminal 3 respectively. The connection method and glue sealing process are the same as steps S3 and S4 in Example 10.

[0111] S5. Reliability testing: Same as in Example 10.

[0112] Example 14

[0113] A method for preparing a flexible liquid-based conductive wire harness using gallium indium tin liquid metal paste as the conductive medium.

[0114] S1. Preparation of Liquid Conductive Slurry: High-purity (≥99.99%) gallium, indium, and tin raw materials were weighed according to the mass ratio of Ga 68.5wt%, In 21.5wt%, and Sn 10wt%. The three metal raw materials were placed in a vacuum melting furnace with a vacuum degree ≤1×10⁻³Pa. The mixture was heated to 170℃ and stirred for 45 min to fully melt and alloy the three metals. After natural cooling to room temperature, a gallium-indium-tin ternary liquid metal alloy slurry was obtained. The obtained slurry was placed in a vacuum degassing device with a vacuum degree of -0.095MPa, a degassing temperature of 25℃, and a degassing time of 15 min.

[0115] S2, grout injection to S5, reliability test: Same as steps S2 to S5 in Example 10.

[0116] Example 15

[0117] A method for preparing flexible liquid-based conductive wire harnesses using modified MXene highly conductive organic slurry as the conductive medium.

[0118] S1. Preparation of liquid conductive paste: Alkylated modified Ti3C3T x MXene nanosheets were dispersed in a high-boiling-point, low-temperature resistant compound organic solvent, with an alkylated modified MXene nanosheet mass fraction of 4.0%. The dispersion was ultrasonicated for 20 min. Conductive carbon black was added as an auxiliary conductive agent, with the amount of conductive carbon black being 10% of the MXene mass. The mixed slurry was then milled and dispersed five times in a three-roll mill until the slurry fineness was ≤10 μm. The milled slurry was then placed in a vacuum degassing device at a vacuum degree of -0.095 MPa, a degassing temperature of 25℃, and a degassing time of 20 min to obtain a modified MXene highly conductive organic slurry.

[0119] S2, grout injection to S5, reliability test: Same as steps S2 to S5 in Example 10.

[0120] Explanation of parameter range

[0121] In Examples 10 to 15 above, the specific values ​​of each process parameter are merely illustrative. Those skilled in the art should understand that the process parameters for each step can be adjusted within the following ranges according to actual conditions: the vacuum degree for vacuum degassing can be -0.08 MPa to -0.1 MPa, the degassing time can be 10 min to 30 min, and the degassing temperature can be 20℃ to 40℃; the vacuum degree for vacuum infusion can be -0.08 MPa to -0.1 MPa, the infusion time can be 5 min to 30 min, and the infusion temperature can be 20℃ to 40℃; the infusion pressure can be 0.12 MPa to 0.2 MPa; the curing process can employ a two-stage curing regime: pre-curing at 60℃ for 60 min followed by curing at 80℃ for 120 min. Any value within the above parameter range can achieve the technical effects of the present invention.

[0122] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any modifications to the technical solutions described in the foregoing embodiments, or equivalent substitutions of some or all of the technical features thereof, within the spirit and principles of the present invention, do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. A flexible liquid-based conductive wire harness, characterized in that, It includes an elastic tube (1) and a liquid conductive slurry (2) injected into the elastic tube (1); the two ends of the elastic tube (1) are respectively provided with terminals (3), and the terminals (3) are electrically connected to the liquid conductive slurry (2); the inner wall of the elastic tube (1) is provided with micron-level spiral grooves (4), which are used to bind the liquid conductive slurry (2) by capillary force when the elastic tube (1) is stretched, so that the liquid conductive slurry (2) is continuously distributed in the inner cavity.

2. The flexible liquid-based conductive wire harness according to claim 1, characterized in that, The terminal (3) is provided with a conductive pin (31) at its tail end. The conductive pin (31) is inserted into the inner cavity of the elastic tube (1) and is in contact with the liquid conductive slurry (2) to achieve electrical conduction. The tail end of the terminal (3) is fixedly connected to the end of the elastic tube (1) by a clamp (5). A potting adhesive layer is provided at the connection between the clamp (5) and the elastic tube (1) to seal the end of the elastic tube (1).

3. The flexible liquid-based conductive wire harness according to claim 1 or 2, characterized in that, The elastic tube (1) is a silicone tube with an inner diameter of 0.5mm to 10mm and a wall thickness of 0.3mm to 2.0mm. The micron-level spiral groove (4) has a depth of 10μm to 200μm, a width of 20μm to 300μm, a pitch of 0.5mm to 5mm, and a cross-sectional shape of V-shaped, U-shaped, semi-circular, or trapezoidal.

4. The flexible liquid-based conductive wire harness according to claim 1 or 2, characterized in that, The liquid conductive paste (2) is a gallium-indium-tin ternary liquid metal alloy with an alloy ratio of Ga 68.5wt%, In 21.5wt%, and Sn 10wt%; or the liquid conductive paste (2) is a modified MXene high-conductivity organic paste, wherein the modified MXene is alkylated Ti3C2T x MXene is dispersed in organic solvent systems resistant to high and low temperatures.

5. The flexible liquid-based conductive wire harness according to claim 1 or 2, characterized in that, The liquid conductive paste (2) is a gallium indium tin-MXene dual-phase composite liquid conductive paste, comprising: Alkylation-modified Ti3C2T x MXene nanosheets, with a mass fraction of 2.0%–5.0%; Micrometer-sized gallium indium tin liquid metal droplets, with a mass fraction of 10.0%–20.0%; Nano-silver wetting agent, with a mass fraction of 0.2% to 1.0%; Halogen-free thermally conductive and flame-retardant composite filler, with a mass fraction of 4.0%–8.0%; High-boiling-point, low-temperature resistant compound with organic solvent, the balance being [amount not specified].

6. The flexible liquid-based conductive wire harness according to claim 5, characterized in that, The alloy ratio of the gallium indium tin liquid metal microdroplets is Ga 68.5wt%, In 21.5wt%, and Sn 10wt%, and the particle size of the gallium indium tin liquid metal microdroplets is 2μm to 15μm; the alkylated modified Ti3C2T x The MXene nanosheets have a transverse dimension of 0.3 μm to 2 μm and a thickness of 1 nm to 5 nm; the nano-silver wetting agent is spherical nano-silver particles with a particle size of 20 nm to 80 nm; the halogen-free thermally conductive and flame-retardant composite filler is a composite system of hexagonal boron nitride powder and ultrafine aluminum hydroxide powder, with a mass ratio of hexagonal boron nitride to ultrafine aluminum hydroxide of 1:1.5 to 1:

3.

7. The flexible liquid-based conductive wire harness according to claim 6, characterized in that, The elastic tube (1) is provided with multiple tubes, which are arranged in a regular manner, covered with an elastic encapsulation layer on the outside and integrally formed into an integrated tube bundle; each elastic tube (1) independently forms a conductive channel.

8. The method for preparing the flexible liquid-based conductive wire harness according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Slurry pretreatment: The liquid conductive slurry (2) is placed in a vacuum degassing device for degassing treatment to remove air bubbles inside the slurry; S2, Slurry injection: Seal one end of the elastic tube (1) and connect the other end to a vacuum injection device to inject the degassed liquid conductive slurry (2) into the inner cavity of the elastic tube (1) under negative pressure; S3, clamp connection: insert the tail of the terminal (3) into the end of the elastic tube (1), and put a clamp (5) on the end of the elastic tube (1) for positioning and clamping. S4. Sealing with glue: Glue is injected at the connection between the clamp (5) and the elastic tube (1) and cured to form a potting glue layer; S5. Reliability Testing: Perform high and low temperature cyclic aging tests, reciprocating tensile fatigue tests, conduction resistance stability tests, and sealing leakage tests on the assembled wire harness.

9. The method for preparing the flexible liquid-based conductive wire harness according to claim 8, characterized in that, In step S2, the vacuum degree of vacuum infusion is -0.08MPa to -0.1MPa, the infusion rate is 10 to 80 mm / min, and the infusion temperature is 20℃ to 40℃.

10. The method for preparing the flexible liquid-based conductive wire harness according to claim 8, characterized in that, In step S4, the sealant is a two-component flexible polyurethane potting compound with a potting pressure of 0.12MPa to 0.2MPa, pressure holding for 30s after potting, and a curing process of pre-curing at 60℃ for 60min followed by curing at 80℃ for 120min.